Through the looking-glass and what Alice found there - Carroll, Lewis; Tenniel, John, Sir, 1820-1914 (Mineola, New York : Dover Publications Incorporated, 1999)
Presents the this sequel to "Alice in Wonderland," wherein Alice goes through the mirror to find a strange world where curious adventures await her.
Originally published in 1872.
6.1
5-8.
5-8
Keywords: Alice (Fictional character : Carroll) -- Fiction; Alice (Fictitious character : Carroll) -- Fiction; Fantasy fiction; Fantasy; Fantasy fiction